Motion analysis of the mandible: guidelines for standardized analysis of computer-assisted recording of condylar movements = Bewegungsanalyse des Unterkiefers : Bewertungskriterien für die standardisierte Auswertung computerassistiert aufgezeichneter kondylärer Bewegungen - Ahlers, Marcus Oliver; Bernhardt, Olaf; Jakstat, Holger A.; Kordaß, Bernd; Türp, Jens C.; Schindler, Hans J.; Hugger, Alfons (International journal of computerized dentistry, 2015)
Mandibular movement recording has long been established as the method for the physiological design of indirect dental restorations. Condylar movement recording is the basis for individual, patient-specific programming of partially or fully adjustable articulators. The settings derived from these recordings can generally be used in both traditional mechanical and electronic virtual articulators. For many years, condylar movement recordings have also provided useful information about morphological conditions in the temporomandibular joints (TMJs) of patients with masticatory system dysfunction based on the recorded movement patterns. The latest clinical application for recorded jaw-motion analysis data consists of functional monitoring of the patient as a diagnostic and surveillance tool accompanying treatment. Published parameters for the analysis of such recordings already exist, but a standardized and practicable protocol for the documentation and analysis of such jaw-movement recordings is still lacking. The aim of this article by a multicenter consortium of authors is to provide an appropriate protocol with the documentation criteria needed to meet the requirements for standardized analysis of computer-assisted recording of condylar movements in the future.
Gesehen am 17.05.2021
Eine frühere Fassung des Beitrags ist im J CranioMand Func 2014;4:333-352 erschienen. Die vorliegende Fassung wurde von den Autoren umfassend überarbeitet und erweitert
Kein DOI vorhanden